Earnings Dispersion, Risk Aversion and Education - Christian Belzil; Jörgen Hansen (Institute for the Study of Labor (IZA), 2002)
We estimate a dynamic programming model of schooling decisions in which the degree of risk aversion can be inferred from schooling decisions. In our model, individuals are heterogeneous with respect to school and market abilities but homogeneous with respect to the degree of risk aversion. We allow endogenous schooling attainments to affect the level of risk experienced in labor market earnings through wage dispersion and employment rate dispersion. We find a low degree of relative risk aversion (0.9282) and the estimates indicate that both wage and employment rate dispersions decrease significantly with schooling attainments. We find that a counterfactual increase in risk aversion will increase schooling attainments. Finally, the low degree of risk aversion implies that an increase in earnings dispersion would have little effect on schooling attainments.
Keywords: J3; J2; 330; dynamic programming; returns to education; risk Aversion; human capital; earnings dispersion; Lohnstruktur; Bildungsertrag; Bildungsverhalten; Nutzenfunktion; Dynamische Optimierung; Risikoaversion; Schätzung; Theorie; Vereinigte Staaten